Analyses of rainfall rate during Malaysian 2014 flood event - Basri, Atikah Balqis; Ismail, Ahmad Fadzil; Khairolanuar, Muhamad Haziq; Sobli, Nuurul Hudaa; Hasan, Mohammad Kamrul; Badron, Khairayu (Science and Engineering Research Support Society, 2016)
An analysis based on rainfall rate characteristics has been carried out to estimate flood occurance. In this paper, we analyzed the rain gauge data for 5 different rain gauge stations. 14 days acquired data covering events before, during and after the flood tragedy in Malaysia. The analysis of the rain gauge data was processed on precipitation phenomena observed in year 2014 in Kota Bharu, Kelantan (Malaysia) from 13 December until 26 December. The data was acquired from the Malaysian Drainage and Irrigation Department (DID). The objective of the research is to derive the tropical flood estimation model using rain gauge data in Malaysia. Among the preliminary result shows that the average rainfall rate at kota bharu is 204.5 mm/hr during the flood tragedy